Grains processing in kano State of Nigeria : Final report and proposals - Center for Agricultural Development Agency (Ibadan : Center for Agricultural Development Agency, 1981)
This report examines the effects of grain processing in Kano State. The study highlight processes which include planting period, storage type, modern technology, harvesting and marketing structure in place.
asm; 15/04/19
Loans
Keywords: Grains processing; Kano State--Nigeria